An examination of rockshelter palynology: Carpenter's Gap 1, northwestern Australia. (August 2020) - Rowe, Cassandra; O'Connor, Sue; Balme, Jane
Carpenter's Gap 1 is a large rockshelter located within the Kimberley region of northwestern Australia. The site provides valuable archives of late Quaternary palaeoecological information within an area known for a lack of deposits preserving long-term continuous botanical records. Previous studies of the macrobotanic, phytolith and wood charcoal records from Carpenter's Gap 1 are in general agreement about changes in broad vegetation patterns over time but differ in the time scales used, in the representation of some species, and in the interpretation of changes – particularly on the degree to which the variations in the record represent cultural activities. An examination of palynology (the transport, deposition and preservation of pollen within the rockshelter environment) provides more detail to the vegetation patterns identified in these previous studies. In addition, because the pollen most likely reflects the vegetation of the site's surrounds over time rather than plants introduced into the shelter by people, interpretation can be more confidently linked to environmental change, and by inference climatic conditions. The pollen data reveal pre-glacial mixed wooded vegetation. From the beginning of the Holocene, tree loss occurred in a transition from monsoonal forest to thicket and eucalypt forest to woodland. Vegetation transition around the mid Holocene suggests a shift in climate, becoming drier and more variable towards and into the late Holocene. The role of fire in the establishment of vegetation communities remains under investigation.